2014
DOI: 10.7213/academica.12.02.ao01
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização dos sistemas de produção de leite de cabra no município de Monteiro, Cariri da Paraíba

Abstract: Objetivou-se com esse trabalho fazer uma caracterização dos sistemas de produção de leite de cabra no município de Monteiro (PB). As informações foram obtidas por meio da aplicação de questionário composto por perguntas referentes à propriedade, rebanho, produção e manejo, do tipo entrevista estruturada. Os resultados demonstraram que 64,7% (110/170) do total das propriedades do estudo pertenciam aos próprios produtores de leite. Com relação ao tamanho, foi observado que 66,4% (113/170) das propriedades possuí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
2
2
0
6
Order By: Relevance
“…These results are consistent with the results of Silva et al (2013) in the municipalities of Cariri, Paraíba, where 68.7% of the producers lived on the farm, while 31.3% lived in the urban area and visited their herds daily. The place of residence of the producer is relevant, since it contributes to increasing the time dedicated to the activity, thereby facilitating identification and solution of problems, consequently resulting in a better administration (HOLANDA JUNIOR;CAMPOS, 2003).…”
Section: Resultssupporting
confidence: 82%
“…These results are consistent with the results of Silva et al (2013) in the municipalities of Cariri, Paraíba, where 68.7% of the producers lived on the farm, while 31.3% lived in the urban area and visited their herds daily. The place of residence of the producer is relevant, since it contributes to increasing the time dedicated to the activity, thereby facilitating identification and solution of problems, consequently resulting in a better administration (HOLANDA JUNIOR;CAMPOS, 2003).…”
Section: Resultssupporting
confidence: 82%
“…In the State of Sergipe, it was observed that the number of animals per property, in the vast majority of cases, was considered small, with up to 50 heads (46.3% and 24.0%) or varying between 50 and 100 animals (34.2 % and 25.0%), in goat and sheep herds, respectively (Table 1). The results corroborate with other regions of the Northeast, such as in the municipality of Sumé, region of Western Cariri in the state of Paraíba, where 49/60 (81.6%) of goat milk producers had herds with up to 50 heads (SILVA et al, 2013), and in 26 properties intended for sheep breeding in the State of Alagoas, where 38.46% of the farmers had 50 animals on the property, while 26.92% reported that they had between 50 and 100 heads (PINHEIRO JÚNIOR et al, 2010).…”
Section: Resultssupporting
confidence: 87%
“…Goat farming in northeastern Brazil is characterized by production based on family or subsistence farming, for domestic consumption and serving the local informal trade (PINHEIRO et al, 2000). Due to the lower socioeconomic level of the breeders, it is natural that the territorial dimensions of the properties are small, as can be seen in the Cariri da Paraíba region (RIET-CORREA et al, 2013;SILVA et al, 2013), the semiarid zone of the state of Pernambuco (DINIZ et al, 2014; RODRIGUES; COELHO; COELHO, 2016), and in Bahia (QUINZERO et al, 2011; PORTO; SALUM, ALVES, 2013), not exceeding 100 ha per family unit.…”
Section: Methodsmentioning
confidence: 99%
“…Em Pernambuco também predominou o sistema de criação extensivo (Almeida et al, 2006). Já no Cariri (Silva et al, 2013b) e na região semiárida da Paraíba (Riet-Correa et al, 2013), o sistema de criação predominante foi o semi-extensivo.…”
Section: Discussionunclassified
“…A suplementação com ração e utilização de capineiras ou silagem também era uma prática pouco habitual. Isso pode ocorrer devido às condições climáticas da região, já que mesmo no período seco as chuvas são frequentes, o que não interfere na disponibilidade de forragem, ao contrário do que ocorre em outras regiões do Brasil, onde a suplementação com ração e o armazenamento de forragem são práticas necessárias durante períodos de estiagem (Bandeira et al, 2007;Santos et al, 2011;Riet-Correa et al, 2013;Silva et al, 2013b).…”
Section: Discussionunclassified